PODEMOS: A Student-Led International Medical Brigade - Thomas Mason; Nayanika Challa; Jae Baek; Arthur Pollauf; Emily Veach; Luis Regalado; Jacy Leon (Journal of Student-Run Clinics, 2021)
PODEMOS, Spanish for â€œWe Canâ€, is an interdisciplinary healthcare organization based in Columbus, Ohio, that is designed to meet the healthcare needs of communities around the city of El Progreso, Honduras. Honduras is a developing country in Central America that scores low in most indicators of healthcare quality and access. Most notably, there is a tremendous need for expanded access in rural communities. Established in 2008 by students from the Ohio State University College of Medicine, PODEMOS conducts biannual medical brigades that run primary care clinics in three rural communities around El Progreso through the volunteer service of United States (US)-based medical, pharmacy, and dental professionals. Additionally, the organization works with local leaders to provide healthcare services for patients with chronic conditions, fill gaps in US-based provider coverage, and recruit patients. PODEMOS bases its care on two models, the acute care model for common adult complaints and all children under the age of 18, and the chronic care model for a subset of adult patients who need more complex care for chronic conditions such as diabetes mellitus and hypertension. Providers then have access to select laboratory and pharmacy services for their patientâ€™s needs. PODEMOS has had a large impact on local communities since its inception, as evidenced by the numerous acute patient visits in its 11 years of existence and the 136 patients currently enrolled in chronic care program. Nevertheless, the organization continues to face challenges in areas such as interprofessional collaboration, security, and maintaining patient turnout. This piece is a descriptive report on PODEMOS, a student-run international medical organization based out of the Ohio State University Wexner Medical Center, that seeks to inform other student-run organizations about the organizationâ€™s structure and operation.